2015
DOI: 10.1099/jmm.0.000083
|View full text |Cite
|
Sign up to set email alerts
|

Genital carriage of the genus Haemophilus in pregnancy: species distribution and antibiotic susceptibility

Abstract: Recent reports have hypothesized that colonization of the maternal genital tract with noncapsulated Haemophilus influenzae could result in neonatal invasive disease. In this study, genital carriage of the genus Haemophilus was investigated in 510 pregnant women attending an Italian hospital for routine controls. Overall, vaginal carriage of the genus Haemophilus was 9.0 % (46/510). A high colonization rate with Haemophilus parainfluenzae (37/510, 7.3 %) was found; other species, such as Haemophilus pittmaniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…Although the literature to date is relatively sparse, H. parainfluenzae is also a species of concern with respect to mother-to-infant infections and APO [44][45][46][47]. Our findings further support the hypothesis that P. gingivalis-induced dysbiosis results in an oral microbiome profile that permits colonization of potential pathogens and favors an increase in population proportion of resident opportunistic pathogens, increasing the overall risk of microbial infection-associated APOs.…”
Section: Introductionsupporting
confidence: 76%
“…Although the literature to date is relatively sparse, H. parainfluenzae is also a species of concern with respect to mother-to-infant infections and APO [44][45][46][47]. Our findings further support the hypothesis that P. gingivalis-induced dysbiosis results in an oral microbiome profile that permits colonization of potential pathogens and favors an increase in population proportion of resident opportunistic pathogens, increasing the overall risk of microbial infection-associated APOs.…”
Section: Introductionsupporting
confidence: 76%
“…[15][16][17] According to this, mutation analysis of QRDRs showed that all strains in this study carried changes at the same positions of GyrA (Ser84 and Asp88) and ParC (at Ser84). The amino acid substitutions found are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ser84Phe has been reported previously in H. parainfluenzae linked to resistance to fluoroquinolones, and Ser84Tyr has been detected in H. parasuis isolates. 5,[16][17][18] All strains showed the Asp88Tyr substitution also found frequently in quinolone-resistant Haemophilus spp. isolates, including H. parainfluenzae.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterium is notorious for β-lactamase production, and its β-lactamase producing ability is typically mediated by transferable plasmids. 17,[24][25][26] H. parainfluenzae is also considered as the origin and reservoir for the dissemination of β-lactamase-carrying plasmids to other bacterial species. 27 The β-lactamases detected include the TEM-1 and TEM-15 types, which are usually associated with plasmids.…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%
“…Some of the substitutions detected included Ser84Phe and Asp88Tyr in gyrA, Ser84Phe, Ser84Leu, Ser84Tyr, Ser138Thr and Met198Leu in parC, and Asp420Asn and Ala451Ser in parE. Of the studies that investigated the involvement of plasmid mediated resistance genes (qnrA, qnrB, qnrS, qnrC, qnrD, qnrVC, qepA and aac(6′)-Ib-cr genes), 15,17,19,20,34 only one detected aac(6′)-Ib-cr in four isolates of H. parainfluenzae.…”
Section: Quinolonesmentioning
confidence: 99%